If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -6x = 15 Reorder the terms: -6x + 2y = 15 Solving -6x + 2y = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -6x + 2y + -2y = 15 + -2y Combine like terms: 2y + -2y = 0 -6x + 0 = 15 + -2y -6x = 15 + -2y Divide each side by '-6'. x = -2.5 + 0.3333333333y Simplifying x = -2.5 + 0.3333333333y
| 7+47z=14z^2 | | 25x^2+12x-15=0 | | 29x-10-13x=4(4x-3)+2 | | 7+44z=35z^2 | | x+250=2x | | 12.50n+35=15.00n+22.50 | | 1.25r+37=2.00r+19 | | 5a+1=a+1 | | x^2=81x | | 8(x-6)=5 | | 8(x-6)=0 | | x^2+17+20=0 | | 3x^2+35x-9.5=0 | | 25x^2-x=0 | | y^2+2y+20=0 | | -3x^2+27x=0 | | 7[9-7(8-b)]-9=9[7(9b-8)+6]-82 | | 17(3m+2)= | | 5x-7(x-8)=48 | | c=2.02w+15.83 | | 18(n+1)= | | (9x^3-4x^2-7)+(-2x^3-2x-4)=0 | | a^2+1=25 | | =5x^2-8x-4 | | =27x^2-90x+27 | | 9x^2+12x+4=12 | | (n+9)+1= | | =3x^2-x-2 | | x(-3x+7)=21 | | 5y+-3x=5 | | -x^2+4=9x+1 | | 7(x+4)= |